Analysis of Economic Activities in Islamic Boarding Schools to Support Welfare in the Tulang Bawang Islamic Boarding School - Anwar Mahmudi; Ari Purnomo; Leni Leni (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
The many aspects of the needs that exist in boarding schools such as building construction, management incentives, proper sanitation, health insurance for students and administrators and a guarantee of a healthy food menu. All of these things certainly require a large budget of funds, but with the condition of the community in the middle to lower economy, the pesantren must reduce the cost of education as little as possible. So that pesantren run independent economic businesses to support these needs, so in this study researchers tried to analyze these economic activities in an effort to improve the prosperity of Islamic boarding schools in Tulang Bawang. This research uses qualitative field methods, the purpose of the research is to know the management and role of pesantren economic activities in efforts to improve the prosperity of pesantren. The conclusion of the results showed that the five pesantrens studied had more than one business, the results of the business had a role in helping the cost of maintaining existing facilities and becoming a place of entrepreneurial practice for students but had not been able to contribute to improving the prosperity of pesantren administrators.